BUSINESS AND ENTREPRENEURSHIP IN THE GREEN ECONOMY IN UZBEKISTAN - Rustamova Dilsabokhon Djuraevna (Ecominds Press, 2025)
The "green" economy is an important direction aimed at ensuring environmental protection and balanced economic development, and this article analyzes the process of green economic transition in Uzbekistan, its impact on business and entrepreneurship.
Keywords: Green economy, green energy, environmentally friendly products, organic products, biofuels.